Business strategy for the development and marketing of handmade soap - Méndez Bravo, Julio César; Lértora Torres, Ivanna Alejandra; Yánez Valarezo, Josselyne Andreina (Ingeniería Química y Desarrollo, 2024)
This article analyzes the creation of a business dedicated to the production and marketing of children's soaps based on glycerin located in the city of Guayaquil, based on the design of a business plan. The objective of the work is to present an efficient proposal for the idea of a business that provides a quality product and that benefits consumers by creating a culture of hygiene in the minors of the home. In which a qualitative methodology was proposed through exploratory, descriptive and field research, for which a market study was carried out to analyze the tastes and preferences of the target market; establishing marketing mix strategies which allowed us to conclude with a viable and sustainable business, which can be replicated by new entrepreneurs and innovators.
Keywords: Production; Hygiene Culture; Quality; Personal Care; Market